Ultrasound-Guided Central Venous Catheterization. Study Guide (Global Journal of Medical Research, 2021)
Central venous catheterization consists of the insertion of a catheter into the central vascular space for diagnostic or therapeutic purposes. Current evidence recommends the use of ultrasound guidance for the insertion of central venous catheters (CVCs), enabling real-time visualization of the procedure while increasing safety and probability of success. It also reduces intervention time and complications. This literature review article presents the advantages, contraindications, procedure technique and most frequent complications of Doppler ultrasoundguided central venous catheterization.
Keywords: central venous catheters ultrasonography; interventional